Three‐dimensional numerical modeling of the Bulle effect: the nonlinear distribution of near‐bed sediment at fluvial diversions. Issue 14 (7th August 2017) - Dutta, Som; Wang, Dongchen; Tassi, Pablo; Garcia, Marcelo H.
Abstract: The Bulle effect is a phenomenon in which a disproportionately higher amount of near‐bed sediment load at a fluvial diversion moves into the diverted channel, even for cases in which the proportion of water (with respect to the main flow) entering the diversion channel is relatively small. This phenomenon has wide‐ranging implications for both engineered and natural systems: from efficient design of channels to redirect water and sediment for reclaiming sinking deltas, designing navigational channels that do not need frequent dredging, to morphological evolution of river bifurcations. The first ever, and one of the most extensive set of experiments conducted to explore this phenomenon, were conducted by Bulle in1926 . In the current study the experiments conducted by Bulle have been simulated using an open‐source, free‐surface finite‐element‐based hydrodynamic solver. The main objectives were to explore to what extent the complex phenomenon of the Bulle effect at the scale of a laboratory experiment can be simulated accurately using Reynolds‐averaged Navier–Stokes (RANS)‐based hydrodynamic solver, and to understand the details of the hydrodynamics that Bulle could not analyze through his experiments. The hydrodynamics captured by the simulations were found to match the observations made by Bulle through his experiments, and the distributions of sediment at the diversion predicted by the numerical simulations were found to match the general trend observed in the laboratory experiments. The results from the numerical simulations were also compared with existing one‐dimensional models for sediment distribution at bifurcations, and the three‐dimensional numerical model was found to perform appreciably better. This is expected due to the complex flow features at the diversion, which can only be captured satisfactorily using a three‐dimensional hydrodynamic model. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Based on experiments on river‐diversions, Bulle in 1926 documented the phenomenon of preferential movement of bedload into the lateral‐channel, often referred to as the Bulle‐Effect. A 3D hydrodynamic model, and a bedload transport model were used to simulate Bulle's experiments. Most of the flow near the bottom was found to move into the lateral‐channel, even though the total flow was divided equally. Due to complex flow‐fields, 3D model was found to predict the sediment distribution better than existing 1D models.